Continuous Reading and Change in the Spatial Configuration of Native Houses of Shiraz (Zandieh and Qajar) Using Quantitative Data with UCL Depth Map Software - Mohammad Bazaei; Maryam Ghasemi Sichani; Alireza Shojaei; Mehdi Madahi (هنر اسلامی, 2020)
Most theorists of architecture believe that culture is one of the factors influencing home design. The spatial configuration of a house in an area can support or disrupt the culture of the inhabitants. Hence, the shape of the house in indigenous architecture is an expression of understanding the content of human life. The necessity of this research is explained based on the dimensions of family and social life. The houses of the Zandieh and Qajar dynasties of Shiraz, which are mostly located in the Sang-e Siah neighborhood, form the statistical population of this research which is of a diverse kind. The aim of this study is to read the spatial organization of the native houses of the old texture of Shiraz accomplished by Space Syntax and the graphical analytical analysis (SPSS) software. Based on the logical arguments gained from the little information obtained from the graphs output of the Ucl Depth Map software, the strengths and weaknesses of the native houses were examined. By analyzing the attained information, a suitable model was extracted in terms of socio-cultural concepts involving the ancient elements. According to the results of the research, by combining the model obtained from this research with modern residential replicas, an innovative prototype can be presented for the imminent houses of the historical cities of Iran. Research objectives 1. Investigating the organization of the native houses of the old texture of Shiraz city 2. Explaining a suitable model for contemporary housing based on the ancient analysis of the models of Zandieh and Qajar period houses in Shiraz. Research question 1. How has culture (residential and social) affected the formation of the Space Organization of Shiraz Houses (Zandieh and Qajar)? 2. What is the role of architects and planners in the present age in perpetuating the socio-cultural values of indigenous environments? To what extent are design software involved in this area?